Wet torrefaction of palm oil mill effluent as an emerging technology for biohydrogen production: An optimization study - Yu, Kai Ling; Zainal, Bidattul Syirat; Mohamed, Hassan; Ker, Pin Jern; Ong, Hwai Chyuan; Zaman, Halimah Badioze; Abdulkareem-Alsultan, Ghassan; Taufiq-Yap, Yun Hin (Elsevier, 2024)
Addressing environmental challenges posed by palm oil mill effluent (POME) waste, wet torrefaction emerges as a pretreatment thermochemical technology towards biomass enhancement for subsequent alternative bioenergy production. An optimization study on the wet torrefaction pretreatment of POME was carried out using response surface methodology to determine the optimum conditions for biomass properties enhancement towards subsequent biohydrogen production. The study showed that the wet torrefaction pretreatment at 180 °C, 10 min holding time and 70% POME to water ratio is the optimum condition to produce a maximum total reducing sugar concentration of 4.05 g/L. The biohydrogen production with 112.4 mL H2/day hydrogen production rate (HPR) and a total 79% chemical oxygen demand (COD) removal efficiency were achieved. Integrating pretreatment and primary treatment processes on converting POME waste to biohydrogen provides insights for sustainable waste utilization, offering a water-efficient and eco-friendly approach in the palm oil industry. © 2024 Hydrogen Energy Publications LLC